Energy Cultures in the European Union - Rosicki, Remigiusz (Przegląd Strategiczny, 2016)
The main objective of the text is to present an analysis that points to the existence of special “energy cultures” in the European Union. The comparative analysis encompassing the results of previous research into “energy cultures” employs statistical methods, i.e. a cluster analysis (Ward’s clustering method and k-means clustering method). The main sections of the text address: (1) the concept and examples of “energy cultures”, (2) a methodology of analysis, (3) aselection of indexes characterising “energy cultures”, (4) an attempt at grouping the European Union member states with the aid of clustering, (5) conclusions. With a view to making the research problem more specific, the present text features the following questions: (1) Is the claim that the European Union manifests special ‘energy cultures’ legitimate?, (2) Did the decade of 2001-2011 witness changes in the field of the European Union ‘energy cultures’, as earlier recognised by the literature?